Determinants of the Success of E-Faktur Tax Application Implementation: A Quantitative Study - Muhammad Nur; Hastuti Mulang; Rosmawati (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2025)
This study aims to analyse the factors that influence the success of e-Faktur application implementation, such as the role of perceived usefulness, perceived ease, and perceived complexity in influencing the level of acceptance and use of digital taxation systems among taxpayers at the Tax Counselling and Consultation Service Office (KP2KP) in Sungguminasa. This study uses a survey method. Data were collected through a questionnaire distributed to 330 respondents who are users of the e-Faktur application and then analysed using SEM-PLS to test the influence of the three independent variables on the dependent variable. The results indicate that perceived usefulness and ease of use positively and significantly influence the success of e-Faktur application implementation. Perceived complexity has a negative and significant influence on the use of digital tax systems. This study contributes to the development of the Technology Acceptance Model theory.